One versus two visits of endodontic treatment on teeth with apical periodontitis - Juni J. Nugroho (DiscoverSys Inc., 2016)
The microbiological purpose of teeth endodontic treatment with apical periodontitis is to reduce microbes in order to achieve periradicular tissue healing and to prevent microbes recolonized. These are obtained by antimicrobial measures, including chemo-mechanical procedures and intra-canal medication, with root canal obturation steps. One of the problems in endodontic is the planning consideration to give treatment with one or two visits. Performing intra-appointment medication is an absolute measure to promote disinfection and successful treatment. Another purpose of this paper is to provide a reference about one or two visit of endodontic treatment decision making for dental professionals. Root canal system on teeth with apical periodontitis treated in two visits endodontic and calcium hydroxide as the intra-appointment medication achieved better microbiological status than the one treated in one visit endodontic.